A method to evaluate the impact of urbanization on ground temperature evolution at regional scale (Rudarsko-geološko-naftni zbornik, 2018)
The replacement of natural soil and vegetation by artificial surfaces increases temperatures of the surrounding air and subsurface throughout the year, because of indirect solar heating of urban structures, building heat losses and land use change. This phenomenon is called Urban Heat Island and it can be better perceived during night-time, when the city releases the heat accumulated during the day. During day-time, due to relatively small amounts of solar radiation received by urban surface, especially in high-density cities in arid and semi-arid climates, Urban Cool Island can be identified as well. The present work illustrates a mixed probabilistic-deterministic method to estimate ground temperature at shallow depth, starting from information on geology, hydrogeology, climate, but also urban presence, through correlations with global land cover and population density. A dedicated mapping on regular grid has been produced. Results have been compared with ground and aquifer temperature available in the literature, for some representative cities of Italian Peninsula and Alpine Zone. Preliminary validations are encouraging and can be taken as a starting point for more comprehensive mapping of ground temperature evolution at regional scale.